Porosity and pore size distribution of beds composed by sugarcane bagasse and wheat bran for solid-state cultivation - Canedo, Marianny Silva [UNESP]; Figueiredo, Maria Fernanda Santos [UNESP]; Thomik, Maximilian; Vorhauer-Huget, Nicole; Tsotsas, Evangelos; Thoméo, João Cláudio [UNESP] (Elsevier, 2021)
Porosity and pore size distribution are influencing factors of several physical properties of porous media. For solid-state cultivation (SSC), this structural information is also important to determine the free space available for the microbial growth. The aim of this work was to determine the porosity and the pore size distribution of packed beds of pure sugarcane bagasse (SCB) and mixtures of SCB with wheat bran (WB) with and without cultivation with the fungus Myceliophthora thermophila I-1D3b. Computer-aided 2D photographic technique was used to evaluate the changes of the bed porosity due to the fungal growth in a mixture of SCB:WB with weight proportion 7:3 at 75% moisture content after 48 h of cultivation. The results showed a steep reduction of more than 50% of the porosity due to the fungal mycelium. A longitudinal porosity profile was found, and the midsection of the bed was poorly colonized due to the steric hindrance. In the uncultivated beds, no change of the porosity was found when changing moisture content of the samples of SCB and SCB:WB 7:3. A wide pore size distribution was observed for the uncultivated media, with the majority of the voids being too narrow for an adequate fungal growth and quite few, though very large, voids ensuring enough space for the mycelial expanse. X-ray tomography (μ-CT) imaging was used to assess the 3D structure of the bed and the complex network of voids. The 3D images reveal an average porosity quite close to the one obtained using the 2D image analysis. The results here obtained will be of help for more realistic models of heat, mass and momentum transfer to be proposed considering porosity variation and pore size distribution in this SSC system. The 2D technique is quite simple to apply and it is able to provide bulk bed structure, while the 3D technique is sophisticated and will allow detailed microstructure information in future experiments.
Keywords: Digital image analysis; Pore size distribution; Porosity determination; Solid-state cultivation; Sugarcane bagasse; Wheat bran